2007
DOI: 10.1259/dmfr/95125494
|View full text |Cite
|
Sign up to set email alerts
|

Digital radiography in general dental practice: a field study

Abstract: Knowledge of how to handle digital equipment in general dental practice should be improved. A calibrated monitor of good quality should be a given priority, as should proper ambient light conditions. There is a need to develop standardized quality controls for digital dental radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…Previous studies [1][2][3]18 noted that general practice dentists encountered many problems with digital radiography. There are more factors to consider and technical matters to address with digital radiography than with film-based radiography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies [1][2][3]18 noted that general practice dentists encountered many problems with digital radiography. There are more factors to consider and technical matters to address with digital radiography than with film-based radiography.…”
Section: Discussionmentioning
confidence: 99%
“…There are more factors to consider and technical matters to address with digital radiography than with film-based radiography. In one study, 3 general practice dentists reported that the digital radiographic technique was more difficult to understand than film-based radiography and that management of the radiographs involved more work after exposure for the dentists, such as image enhancement and back-up problems. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the international literature many articles can be found describing digital detector systems and presenting comparisons among various systems with regard to their diagnostic performance [5][6][7][8][9]. The characteristics of the x-ray beam, especially the x-ray beam energy, can also contribute to image quality.…”
Section: Introductionmentioning
confidence: 99%